Comparison of stable isotope mixing models for examining plant root water uptake. - Xue Qiu; Mingjun Zhang; Shengjie Wang; Hongfei Meng; Cunwei Che (PLoS ONE)
As natural isotope tracers, δ18O and δ2H have been widely applied to examine the water uptake of plant root, but the various stable isotope mixing models may lead to different explanations. To understand the influence of models, here we selected a typical plant Caragana korshinskii Kom. in northeastern Tibetan Plateau, and analyzed the stable water isotope compositions in plant xylem and potential sources including precipitation and soil water. Three stable isotope mixing models, i.e., IsoSource, MixSIR and MixSIAR were used, and then the differences in the proportional contributions of various water sources for plant root were examined. The results showed that the IsoSource and MixSIR were generally similar, while the MixSIAR were significantly different. Although the proportional contributions of each water source were different due to different algorithms, the water source which contributed maximum proportion was the same for all models. This study provides a scientific reference for the selection of models for the study of plant water use strategies in similar study areas, i.e., the most dominant water source can be identified regardless of the choice of model.